Implementasi Pembelajaran Fiqih Taharah di Majlis Taklim Al Falah Tangerang - Dwi Cahyo; Nurul Hafidz; Dimas Muhammad; Bismi Izul; Asrori Mukhtarom (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Learning Islamic jurisprudence (fiqh taharah) is an important foundation in developing correct worship habits in children. This community service research examines the implementation of Islamic jurisprudence (fiqh taharah) learning at Majlis Taklim Al Falah Tangerang with the aim of improving knowledge, practical skills in ablution, and the capacity of teachers in teaching children. The method used is an asset-based community development (ABCD) approach and a participatory-educational approach that combines short theory sessions, demonstrations, repeated practice, and non-written practical evaluations. Data were collected through observation, interviews, direct practice, and formative evaluations during the activities. The results show an increase in participants' conceptual understanding of hadas and najis (impurity) and improved ablution practical skills, characterized by enthusiasm, the ability to imitate the ablution sequence more accurately, and a positive response to practical learning methods. In addition, the program encourages teachers' awareness to implement skills-based evaluation and enrich learning methods according to children's characteristics. In conclusion, Islamic jurisprudence (fiqh taharah) learning at Majlis Taklim is more effective when it is practice-oriented, participatory, and sustainable; Follow-up recommendations include routine ablution practices, pedagogical training for teachers, and the provision of simple media to support learning.